Editors' Note: Normobaric Hyperoxia Combined With Endovascular Treatment for Patients With Acute Ischemic Stroke: A Randomized Controlled Clinical Trial. (6th December 2022) - Ganesh, Aravind; Galetta, Steven
Abstract : Dr. Li et al. investigated the safety and efficacy of normobaric hyperoxia (NBO) combined with endovascular treatment (EVT), compared with EVT alone, in 86 patients with acute ischemic stroke and large vessel occlusion in the anterior circulation in a single-center, proof-of-concept, assessor-blinded, randomized, controlled pilot study. NBO consisted of giving 100% oxygen through a face mask (10L/min for 4 hours) before vascular recanalization. The researchers found that the infarct volume at 24–48 hours was significantly smaller in the NBO group. In addition, the NBO group had a significantly lower median mRS at 90 days. The paper generated considerable interest from the readership, and several responses were received. In one response, Dr. Yin et al. propose that hyperbaric oxygen therapy (HBOT) could promote greater oxygen diffusion into ischemic tissues as a potential neuroprotective treatment. They suggest that HBOT, delivered in single or multiple sessions to mitigate adverse effects of prolonged exposure, would be a helpful comparator with NBO in future trials. Responding to this comment, the authors cite previous studies suggesting that a single round of HBOT delivered alone or after NBO may be more effective than NBO alone in treating transient ischemia in animal models. However, repeated daily HBOT had no additional benefit in those studies. They speculate that a single round of HBOT with EVT may be optimal. Nevertheless, they emphasize the ease of delivery of NBO compared with the need for a special pressuring device to deliver HBOT, which may result in treatment delays and may be more difficult to achieve while undergoing EVT.